2005
DOI: 10.1002/anie.200500253
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Gold(III) Alkynyl Complexes: Synthesis, Structural Characterization, and Luminescence Properties

Abstract: In contrast to the related gold(i) [1][2][3] and the isoelectronic platinum(ii) compounds, [4,5] which are known to show rich luminescence properties, luminescent gold(iii) compounds are rare, with very few exceptions that emit at room temperature in solution.[6] The reasons for the lack of luminescence in gold(iii) species are probably the presence of low-energy d-d ligand field (LF) states and the electrophilicity of the gold(iii) center. The presence of a nonemissive low-lying d-d state would quench the lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 46 publications
(6 reference statements)
5
128
1
1
Order By: Relevance
“…These orbitals are quite susceptible for thermal population at ambient temperatures which then follows rapid nonradiative relaxation pathways. 2 Here in this work we report the syntheses of stable mononuclear cyclometalated cisgold(III)-σ-dialkynyl complexes and their luminescent properties. ABSTRACT: A series of novel luminescent neutral cyclometalated gold(III) complexes of the type cis-[(N ∧ C)Au(CtCR) 2 ] (R = aryl, silyl groups) having different cyclometalating cores (N ∧ C) have been synthesized by CuI promoted halide to alkynyl metathesis with NEt 3 as in situ deprotonating agent.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These orbitals are quite susceptible for thermal population at ambient temperatures which then follows rapid nonradiative relaxation pathways. 2 Here in this work we report the syntheses of stable mononuclear cyclometalated cisgold(III)-σ-dialkynyl complexes and their luminescent properties. ABSTRACT: A series of novel luminescent neutral cyclometalated gold(III) complexes of the type cis-[(N ∧ C)Au(CtCR) 2 ] (R = aryl, silyl groups) having different cyclometalating cores (N ∧ C) have been synthesized by CuI promoted halide to alkynyl metathesis with NEt 3 as in situ deprotonating agent.…”
Section: ' Introductionmentioning
confidence: 99%
“…Notables among the few known examples include mononuclear gold(III) complexes containing one alkynyl ligand, viz., [Au(CtCCF 3 )Me 2 (L)] and [Au(CtCR)Me 2 (PPh 3 )], 10,11 [Au(C ∧ N ∧ C)(CtCR)], 2,12,13 and three alkynyl ligands [Au (CtCR) 3 4 ] þ [Au(CtCR) 4 ] À . 14,15 Dinuclear gold(I)Àgold(III) complexes bearing two alkynyl ligands, viz., [Au I (μ-{CH 2 }PPh 2 ) 2 Au III (CtCR) 2 ], have also been reported 16 (Figure 1). In general, gold(III) complexes tend to exhibit relatively large positive reduction potentials, 17,18 and the consequent instability is a probable reason for their scarcity.…”
Section: ' Introductionmentioning
confidence: 99%
“…In contrast to the related Au(I) (224,234,(241)(242)(243)(244)(245)(246)(247)(248)(249)(250)(251)(252)(253)(254)(255)(256), and the isoelectronic Pt(II) compounds (16,250,257,258) that show excellent luminescence properties, room temperature luminescent Au(III) compounds are rare with only a limited number of examples known (259)(260)(261). This same trend holds for alkynyl complexes; Au(I) (240-242, 246, 249) and Pt(II) species (16,262,263) are widely known and possess rich photoluminescence properties, while the number Au(III) examples is quite limited (257,259,264,265). The primary reason for this is the low-energy ligand-field states that are capable of quenching the emissive excited state (266).…”
Section: Physical Properties and Electronic Considerationsmentioning
confidence: 99%
“…Additionally, the ease in metal center reduction to Au(I) makes these complexes susceptible to participation in photoinduced electron transfer as a secondary quenching pathway to luminescence. One of the advantages of coupling strong s-donating alkynyl ligands to Au(III) is that the strong bonding interaction raises the energy of the ligand-field states, at the same time decreasing the electrophilicity of the Au(III) center, which enhances the overall luminescence of the compound (259,264). For example, cyclometalated Au(III)-alkynyl compounds 1-5 ( Fig.…”
Section: Physical Properties and Electronic Considerationsmentioning
confidence: 99%
“…In sharp contrast to gold (I), gold(III) alkynyl complexes are relatively uncommon and, to the best of our knowledge, there are no reports of gold(II) alkynyl complexes. Gold(III) complexes of the type [Au(C^CCF 3 )Me 2 (L)] (L ¼ PMe 2 Ph, PPh 3 ) [7e9] and [Au(C^CR)Me 2 (PPh3)] (R ¼ H, Me) have been prepared by Schmidbaur et al [10] and the Yam group reported the first examples of the luminescent behavior of gold(III) alkynyl complexes of the type [Au(C^N^C)(C^CR)] [HC^N^CH ¼ 2,6-diphenylpyridine, R ¼ Ph, C 6 H 4 -Cl-p, C 6 H 4 -OCH 3 -p, C 6 H 4 -NH 2 -p; HC^N^CH ¼ 2,6-bis(4-t-butylphenyl)pyridine, R ¼ Ph] [11]. A series of gold(I)-gold(III) complexes of the type [Au I (m-{CH 2 } 2 PPh 2 ) 2 Au III (C^CR) 2 ] [R]Ph, t Bu, SiMe 3 ] has also been reported, and represents the first fully characterized examples of gold complexes containing two alkynyl ligands bound to a gold(III) center [12].…”
Section: Introductionmentioning
confidence: 99%